2021
DOI: 10.1371/journal.pone.0258268
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with oral pain and oral health-related productivity loss in the USA, National Health and Nutrition Examination Surveys (NHANES), 2015–2018

Abstract: Background Our aim was to identify clinical and sociodemographic factors associated with oral pain and oral health-related productivity loss among US adults. Methods We included adults aged ≥30 years who completed the dental examination, had at least one natural tooth, and provided an answer about their oral pain experience or oral health-related productivity loss in the 2015–2018 National Health and Nutrition and Examination Survey (NHANES). We performed descriptive analyses and multivariable binary logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Dental caries is a highly prevalent infectious bacterial disease, ranking first in prevalence among 328 diseases worldwide in 2016 (Vos et al, 2017). Dental caries can adversely impact the quality of life of affected patients, resulting in complications including pain and, in severe cases, tooth loss (Aldosari et al, 2021;Amarasena et al, 2021;Santos et al, 2021). Streptococcus mutans (S. mutans) is an essential cariogenic bacterium that metabolizes carbohydrates within the oral cavity and thereby lowers the local pH at the tooth surface (Loesche, 1986;OmerOglou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries is a highly prevalent infectious bacterial disease, ranking first in prevalence among 328 diseases worldwide in 2016 (Vos et al, 2017). Dental caries can adversely impact the quality of life of affected patients, resulting in complications including pain and, in severe cases, tooth loss (Aldosari et al, 2021;Amarasena et al, 2021;Santos et al, 2021). Streptococcus mutans (S. mutans) is an essential cariogenic bacterium that metabolizes carbohydrates within the oral cavity and thereby lowers the local pH at the tooth surface (Loesche, 1986;OmerOglou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This study implicates the usefulness of dental check‐ups as health promotion in the workplace. People with acute dental problems are more likely to be absent from work than those without, and absenteeism is especially high when they have oral cavity pain 20 . People with poor oral health are generally more likely to experience acute dental symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…People with acute dental problems are more likely to be absent from work than those without, and absenteeism is especially high when they have oral cavity pain. 20 People with poor oral health are generally more likely to experience acute dental symptoms. Regular dental check‐ups provide the opportunity for early detection and treatment of dental diseases, which improves the oral health of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the factors associated with OP included non-Hispanic Black, lower-income status ( 15 ), depression status ( 16 ), and long working hours ( 17 ). Our study added a new contribution that the thiocyanate exposure was associated with OP, while the perchlorate or nitrate exposure had no relationship with OP.…”
Section: Discussionmentioning
confidence: 99%